EKOLOGI KOMUNITAS MAKROZOOBENTOS SUNGAI UMBULREJO DI KECAMATAN DAMPIT KABUPATEN MALANG - Miftahul Khair Kadim (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
Macrozoobenthos is one of the biota that can be used as bioindicator because it is relatively settled. Water quality changes both chemical and physical consequently changes macrozoobenthos. The objective of this research is to obtain the structure of the community of macrozoobenthos in the River Umbulrejo in order to determine the condition of the river waters quality as well as examine the relationship of community structure of macrozoobenthos and thei ecological. The research was carried out from October to December 2011 at 14 stations observation. Determination of observation stations based on land use the different of around Umbulrejo River. Sampling technique is kicking method in the area of 10 m riflle using hand net with mesh size of 500 µm. Macrozoobenthos samples preserved using alcohol then identified using the key of identification available. Data analysis program using the CANOCO analysis type Canonical Correspondence Analysis (CCA). Macrozoobenthos communities founded at Umbulrejo River, obtained 70 taxa. The lowest number of taxa founded at in station 6 as much as 13 taxa. The highest number of taxa founded at station 14 as much as 35 taxa. Data of current velocity varies of 27 - 104 cm/s; type substrate combination boulder, cobble, pebble, gravel, sand and silt; water temperature of 21-29 °C; pH 7; DO varies of 5,14 - 9,44 mg/l; BOD of 0,01 - 3,43 mg/l; ammonia of 0,02- 0.3 mg/l; and hardness of 50 - 200 mg/l. Structure of the community of macrozoobenthos in the river umbulrejo divided into 2 groups. Group of polluted categories (stations 1, 2, 3, 4,5 and 7) located at the village of Pamotan, percent riparian of 35 – 75 %, width of 2 – 3 m, riffle flow macrozoobenthos which composed by Glossosomatidae, Thiaridae, Sundathelpusidae, Perlidae and Tubificidae. Group of bit heavy polluted categories (station 6, 8, 9, 10, 11, 12, 13 and 14) located at the village of Pamotan, Majang Tengah and Geduk Wetan percent riparian 35 – 50 %, width of 4 -7 m, riffle flow, macrozoobenthos which composed by Caenidae, Chirinomidae, Hirudinae, Tubificidae and Simulidae. Based on the result of the research it is recommended that goverment of village Pamotan to improve the knowledge of the farmers the impact of fertilizer and pesticides to environment.